The Role of Rational Emotive Behavioral Therapy on Students Adjustment - Farideh Hamidi; Farshid Paidar; Farangis Mohammadi (Shiraz University of Medical Sciences, 2017)
Background: Adjustment is one of the factors that promote mental health and academic achievement of students. Objectives: This study examined the role of rational emotive behavior therapy on adjustment among high school male students of Bostan-Abad city. Methods: The method was experimental and the statistical population included all 2nd and 3rd grade high school students of the city of Bostan-Abad enrolled in the academic year 2014 to 2015, that were estimated as 680 students. To select the sample, the adjustment inventory for school students (AISS Singh Sinha, 1993) was completed by 150 students, of whom 30 students met the required conditions, and were divided randomly to two groups (15 in the experimental and 15 in the control group). Rational emotive behavior therapy was conducted during eight sessions. Results: After entering the data into the SPSS20 software, the data were analyzed using analysis of covariance (ANCOVA), which showed that after the intervention, the relationship among general adjustment and its components in the control and experiment group was significant (P < 0.01). In this regard, Rational Emotive Behavior therapy enhances the overall adjustment (F (1, 27)= 15.02, P = 0.001, η P 2= 0.46) among the students. Conclusions: The results indicate that rational emotive behavior therapy improves the overall adjustment and its components in high school male students.